Interdisciplinary Integration of the CVS Module and Its Effect on Faculty and Student Satisfaction as Well as Student Performance - Ayuob Nasra N (BMC Medical Education, 2012)
Abstract Background Beyond the adoption of the principles of horizontal and vertical integration, significant planning and implementation of curriculum reform is needed. This study aimed to assess the effect of the interdisciplinary integrated Cardiovascular System (CVS) module on both student satisfaction and performance and comparing them to those of the temporally coordinated CVS module that was implemented in the previous year at the faculty of Medicine of the King Abdulaziz University, Saudi Arabia. Methods This interventional study used mixed method research design to assess student and faculty satisfaction with the level of integration within the CVS module. A team from the medical education department was assembled in 2010/2011 to design a plan to improve the CVS module integration level. After delivering the developed module, both student and faculty satisfaction as well as students performance were assessed and compared to those of the previous year to provide an idea about module effectiveness. Results Many challenges faced the medical education team during design and implementation of the developed CVS module e.g. resistance of faculty members to change, increasing the percentage of students directed learning hours from the total contact hour allotted to the module and shifting to integrated item writing in students assessment, spite of that the module achieved a significant increase in both teaching faculty and student satisfaction as well as in the module scores. Conclusion The fully integrated CVS has yielded encouraging results that individual teachers or other medical schools who attempt to reformulate their curriculum may find valuable.